Studies on the nucleation of MBE grown Ⅲ-nitride nanowires on Si - 鄂炎雄 郝智彪 余佳东 吴超 汪莱 熊兵 王健 韩彦军 孙长征 罗毅 (Chinese physics B, 2017)
GaN and AlN nanowires（NWs） have attracted great interests for the fabrication of novel nano-sized devices. In this paper, the nucleation processes of GaN and AlN NWs grown on Si substrates by molecular beam epitaxy（MBE）are investigated. It is found that GaN NWs nucleated on in-situ formed Si3N4 fully release the stress upon the interface between GaN NW and amorphous Si3N4 layer, while AlN NWs nucleated by aluminization process gradually release the stress during growth. Depending on the strain status as well as the migration ability of Ⅲ group adatoms, the different growth kinetics of GaN and AlN NWs result in different NW morphologies, i.e., GaN NWs with uniform radii and AlN NWs with tapered bases.